Les Représentations De La Beauté Féminine: Une Lecture Des Fondements Socioculturels Du Teint Clair Chez Les Bété De Côte d’Ivoire - Marcel, Yoro Blé (European Scientific Journal, ESJ, 2017)
This study proposes an analysis of the representation of the female beauty whose clear complexion is one of the illustrations in the bété. In Côte d’Ivoire, the bété shows that there was a development of the beauty through the worship of the bagnon. However, in the representation of the male beauty through the bagnon, there is no fixed color complexion. It is not the same for the beauty of the woman whose clear complexion is of significant importance. This is why this study proposes the canons of the female beauty and to question the sociocultural bases which specifically underlie the preference of the clear complexion to the black complexion of the bété woman. However, this is in a bid to understand the cultural anchoring of the female depigmentation in bété country. From a field survey of people of all social categories, the study shows that the preference of the clear complexion is explained by the fact that it would carry virtues of rejuvenation and longevity for the man. In other words, the beauty of the woman aims at developing the man by rejuvenating him and by lengthening his life expectancy. These imaginations results to the depigmentation of the young girls and women bété in their search for beauty. This they do via the clear complexion to make them more attractive to men.